An Analysis of The Arabic Language Textbook for Grade 11: The Scientific Approach in the 2013 Curriculum - Huda, Ahmad Nawirul; Abdullah, Muhammad Yahya (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Using books as a source of learning is something that teachers usually do. Textbooks serve as study guides for teachers and students. In analysing the Arabic language textbook for the semester, the author states that this book is very suitable as an Arabic language textbook according to BSNP standards, as it scored 82% for content, 97% for presentation, 80% for language, 89% for illustrations, and 86% for overall evaluation. Overall, this book is suitable for use as a textbook in schools. The contents of the book are good in terms of structure, KI and KD, depth of material, and student development. The presentation of the book is also good, despite the lack of a summary of the material, but this shortcoming can be covered by tasks that can be used to enhance student understanding. The language in which the book is written is appropriate for the student's level and is written in a straightforward manner, but it is less interactive. Regardless, the book's illustrations are also appropriate, with the choice of book size, cover colour, and cover image really making it clear that this is an Arabic book, as well as the proportionate format of the book and the correct choice of paper colour, font, and quality. The writing makes readers feel at home when reading it.